Trends in Coffee and Tea Consumption during the COVID-19 Pandemic - Fabio Castellana; Sara De Nucci; Giovanni De Pergola; Martina Di Chito; Giuseppe Lisco; Vincenzo Triggiani; Rodolfo Sardone; Roberta Zupo (Foods, 2021)
Over the last two years, many countries have enforced confinement to limit both the spread of COVID-19 and the demand for medical care. Confinement has resulted in a disruption of work routines, boredom, depression, and changes in eating habits, among them consumption of coffee and tea. Following six databases, we examined articles tracking consumption of these beverages. Out of 472 articles, including 23 beverage entries, 13 matched our criteria. While no clear trend in coffee consumption during the coronavirus pandemic emerged (7 of 13 studies indicated an increase, accounting for 53.8%), tea consumption clearly increased (70% versus 30%). Considering the global health emergency continuum, more research is needed to better understand the paths underlying food choices and the ways those changes may influence health outcomes, including those related to COVID-19 disease.